Structured Number Head Learning Strategy to Increase Elementary School Students' Learning Activeness - Maulida Rizqia; M. Rofi Fauzi; Mustapa Ahmad (Yayasan Zia Salsabila, 2024)
Active learning is a contemporary material that requires teachers to be able to condition students, classes and the learning process. Even though many previous articles discuss active learning strategies, studies that focus on structured number head learning strategies in elementary age children have not yet been discussed in depth. This research seeks to reveal the use of structured number head strategies in natural science learning in elementary school age children. Data collection uses observation, interviews and documentation studies methods. Next, the data was analyzed using data reduction, data display and verification techniques, then its validity was tested using data triangulation techniques. The results of this research conclude that learning the type of numbered head structure for teacher observation is in the good category for increasing the activeness of student learning activities. Because learning with this strategy forms groups that work together to fulfill their respective responsibilities and are interdependent with their peers, as each group can present and explain the results of the discussion according to their understanding. Through the implementation of the numbered head structure strategy, it is hoped that students will have active interest and enthusiasm in participating in the learning process, both in class and outside of class.